Landlord and Tenant Law - Wilkie, Margaret. author. aut Link
XXVI, 206 p.
Keywords: This text aims to provide a comprehensive exposition of the law relating to landlord and tenant. It covers the characteristics of different types of lease, the obligations implied on behalf of the landlord and tenant, the effects of covenants in leases and different types of tenancies.